4-{(E)-2-[4-(But-3-en-1-yloxy)phenyl]diazen-1-yl}Benzoic Acid - Lutfor, M. R.; M. M., Yusoff; Huey, Chong Kwong; Hegde, Gurumurthy; Mohamed Ibrahim, Mohamed Tahir; Mohamad Zaki, Ab Rahman (International Union of Crystallography, 2012)
The title compound, C17H16N2O3, has an E conformation about the azobenzene (–N=N–) linkage. The benzene rings are twisted slightly with respect to each other [6.79 (9)°], while the dihedral angle between the plane through the carboxy group and the attached benzene ring is 3.2 (2)°. In the crystal, molecules are oriented with the carboxy groups head-to-head, forming O—H(...)O hydrogen-bonded inversion dimers. These dimers are connected by C—H(...)O hydrogen-bonds into layers lying parallel to the (013) plane.